A Case of Hereditary Spherocytosis Initially Manifested as an Aplastic Crisis Caused by Parvovirus B19 Infection - Hyungsuk Jin; Ji Won Lee; Hee Young Ju; Hee Won Cho; Ju Kyung Hyun; Ki Woong Sung; Hong Hoe Koo; Hee-Jin Kim; Keon Hee Yoo (The Korean Society of Pediatric Hematology-Oncology, 2020)
Hereditary spherocytosis (HS) is the most common inherited red cell membrane disorder. Its main laboratory finding is anemia with reticulocytosis. However, in the case of an aplastic crisis, there may be no reticulocytosis, making the diagnosis of HS difficult. We present the case of a 4-year-old boy who initially presented with persistent fever and sore throat. His 8-year old brother also had anemia of unknown etiology, and his father had a history of splenectomy in his 20s. Physical examination revealed anemic conjunctivae and hepatosplenomegaly, and laboratory findings showed anemia with decreased reticulocyte count and elevated ferritin and lactate dehydrogenase levels. A peripheral blood smear showed microcytic hypochromic anemia with severe poikilocytosis (spherocytes, acanthocytes, schistocytes), and bone marrow examination revealed decreased erythroid cells and increased hemophagocytosis. Increased osmotic fragility was observed, and parvovirus B19 was detected using polymerase chain reaction. Hence, we established the diagnosis of hereditary spherocytosis manifested as an aplastic crisis caused by parvovirus B19 infection.